Virus taxonomy : ninth report of the International Committee on Taxonomy of Viruses - International Committee on Taxonomy of Viruses; King, Andrew; ScienceDirect eBooks (Oxford : Elsevier, 2011)
The practical need to partition the world of viruses into distinguishable, universally agreed upon entities is the ultimate justification for developing a virus classification system. Since 1971, the International Committee on Taxonomy of Viruses (ICTV) operating on behalf of the world community of virologists has taken on the task of developing a single, universal taxonomic scheme for all viruses infecting animals (vertebrate, invertebrates, and protozoa), plants (higher plants and algae), fungi, bacteria, and archaea. The current report builds on the accumulated taxonomic construction of the eight previous reports dating back to 1971 and records the proceedings of the Committee since publication of the last report in 2005. Representing the work of more than 500 virologists worldwide, this report is the authoritative reference for virus organization, distinction, and structure.
Machine generated contents note: pt. I Introduction -- Introduction to Virus Taxonomy -- Glossary of Abbreviations -- Families and Genera of Viruses Listed According to the Nature of the Genome -- Virus Diagrams -- pt. II The Viruses -- Order of Presentation of Virus Taxonomic Descriptions -- The Double Stranded DNA Viruses -- The Single Stranded DNA Viruses -- The Reverse Transcribing DNA and RNA Viruses -- The Double Stranded RNA Viruses -- The Negative Sense Single Stranded RNA Viruses -- The Positive Sense Single Stranded RNA Viruses -- The Unassigned Viruses -- The Subviral Agents -- Satellites -- Viroids -- Fungal Prions -- Vertebrate Prions -- pt. III The International Committee on Taxonomy of Viruses -- Officers and Members of the ICTV -- Executive Committee ICTV 2008 -- 2011 -- Executive Committee ICTV 2005 -- 2008 -- Life Members ICTV 2008 -- 2011 -- National Representatives 2008 -- 2011 -- ICTV Subcommittees and Study Groups 2011 -- The Statutes of the ICTV, 2008 -- The International Code of Virus Classification and Nomenclature, 2002 -- pt. IV The Indexes -- Virus Index.
Print version record.
Elsevier
Keywords: Viruses -- Classification; Viruses; Viren; Viruses -- classification; Electronic books